THE USE OF PORTFOLIO ASSESMENT TO OVERCOME THE WEAKNESS OF SCIENTIFIC APPROACH - Suarsana, I Made; Putu Supawidhiasih, Ni; Parwati, Ni Nyoman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
This classroom action research was aimed to improve mathematics conceptual understanding of X A UPW SMK Negeri 1 Singaraja after applied scientific approach with portfolio assessment. The subject of this research was 35 students from X A UPW SMK Negeri 1 Singaraja in academic year 2016/2017.The results showed that the application of scientific approach with portfolio assessment improve the mathematics conceptual understanding of X A UPW student of SMK Negeri 1 Singaraja. The mastery learning increase by 22,86% from 37,14% in cycle I to 60% in cycle II and at last increase to 77,14% in cycle III. The students also give positive response to the implementation of scientific approach with portfolio assessment with an average score 46,4. The increasing of student mathematics conceptual understanding happen because scientific approach give big chance to the student to explore and guide them finding the concept, and the portfolio assessment facilitate them to know better their ability so that the student can improve their conceptual understanding.